APLIKASI MIKROORGANISME LIGNOSELULOLITIK INDIGENUS ASAL TANAH GAMBUT RIAU DALAM PEMBUATAN KOMPOS DARI LIMBAH TANDAN KOSONG KELAPA SAWIT (Elaeis guineensis Jacq.) - Jannah, Wirdatul; Delita Zul, Delita Zul; Fibriarti, Bernadeta Leni (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Palm oil industries usually produce side result such as empty fruit bunch (EFB) wastes. This waste can be employed as a substrate for making compost. Naturally, EFB takes a long time to produce standardized compost as its contains lignin and cellulose components. The purpose of this research was to analyze the ability of indigenous lignocellulolytic microorganisms isolated from peat soil in Riau as the bioactivator. The selected isolates consisting of 4 bacteria (BB_S27, BB_HP42, BB_HP41 and BB_K20) and 2 fungi (LIJ1 and L1J2) were subcultured on Nutrient Broth and Potato Dextrose Broth. Starters were then prepared from a combination of those isolates resulting three types of starter, namely starter I (4 isolates bacteria), starter II (4 isolates bacteria and 1 isolates fungi), starter III (4 isolates bacteria and 2 isolates fungi). As positive controls, starter IV (EM4) and starter V (bioactivator made in USA) were utilized. Starters were prepared by fermentation process during 7 days using seedling media. Composting was done by the windrow composting system utilizing 500 kg EFB as a substrate and inoculated by 50 liters of the starters at the 1st and 7th incubation time. During 35 days composting process, the substrate was enriched by water every 2 days. The best quality compost was produced by K3 treatment (a combination of 4 bacteria) as its characters almost in line with the National Quality Standard (ISO) such as N 1.57%, C/N ratio 23.89, P 0.38%, K 1.61%, blackish brown color, soil smell, unraveled texture, and the highest cell number of bacteria, fungi, and celullolytic microorganisms were with value 1.38x1012 CFU/g, 2.08x107 CFU/g dan 1.35x108 CFU/g, respectively.